Salvia cajamarcana (Lamiaceae), a new species from Cajamarca Department, Peru, and lectotypification of S. revoluta - González-Gallegos, Jesús Guadalupe; Roncal-Rabanal, Manuel; Uría, Rolando (Phytotaxa, 2023)
Recent botanical exploration in the Andes in northwestern Peru has led to the discovery of an undescribed species of Salvia. With 78 species of Salvia, Peru ranks second in Salvia richness among American countries behind only Mexico. The most recent comprehensive revision of Peruvian species dates from 1960, so it is highly probable that an updated revision of the genus in the country would entail the description of several new taxa. Accordingly, we present a diagnosis and description of a new species under the name Salvia cajamarcana. This new species is morphologically most similar to S. revoluta, for which a full revised description is presented to facilitate comparison, as well as the designation of a lectotype. Figures and a distribution map are provided to illustrate the morphology and distribution of the species.